2019
DOI: 10.1007/s11920-019-1013-4
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Slow-Wave Activity and Neuroplasticity Impairments in Major Depressive Disorder

Abstract: Purpose of Review In this review, we aim to integrate the most recent research highlighting alterations in sleep slow-wave activity (SWA), and impairments in neuroplasticity in major depressive disorder (MDD) into a novel model of disorder maintenance. Recent Findings Sleep homeostasis has been shown to be impaired in MDD, with a subset of individuals also demonstrating impaired SWA. SWA is considered a marker of the homeostatic regulation of sleep, and is implicated in the downscaling of synaptic strength i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, we previously reported time‐dependent changes in the endogenous expression of IAIPs in the brain after exposure to hypoxia–ischemia and hypoxia alone in neonatal rats (Disdier et al, ) and in the cerebral cortex and cerebellum of fetal sheep after exposure to brain ischemia (Spasova et al, ). Studies have also suggested that IAIPs could be important in neuroplasticity (Duman, Aghajanian, Sanacora, & Krystal, ; Gaudet, Lim, Stonestreet, & Threlkeld, ; Goldschmied & Gehrman, ; Normann, Schmitz, Furmaier, Doing, & Bach, ; Popoli, Gennarelli, & Racagni, ). Other studies have reported that genetically determined variants in the heavy chains of IAIPs are related to psychiatric disorders including schizophrenia and bipolar disorders (Brandl et al, ; Cross‐Disorder Group of the Psychiatric Genomics Consortium, ; Hamshere et al, ; Sasayama et al, ; Schizophrenia Psychiatric Genome‐Wide Association Study Consortium, ) and that mice deficient in bikunin (Ambp/bikunin knockout mice) exhibit specific behavioral phenotypes such as increased anxiety‐like behavior (Goulding et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we previously reported time‐dependent changes in the endogenous expression of IAIPs in the brain after exposure to hypoxia–ischemia and hypoxia alone in neonatal rats (Disdier et al, ) and in the cerebral cortex and cerebellum of fetal sheep after exposure to brain ischemia (Spasova et al, ). Studies have also suggested that IAIPs could be important in neuroplasticity (Duman, Aghajanian, Sanacora, & Krystal, ; Gaudet, Lim, Stonestreet, & Threlkeld, ; Goldschmied & Gehrman, ; Normann, Schmitz, Furmaier, Doing, & Bach, ; Popoli, Gennarelli, & Racagni, ). Other studies have reported that genetically determined variants in the heavy chains of IAIPs are related to psychiatric disorders including schizophrenia and bipolar disorders (Brandl et al, ; Cross‐Disorder Group of the Psychiatric Genomics Consortium, ; Hamshere et al, ; Sasayama et al, ; Schizophrenia Psychiatric Genome‐Wide Association Study Consortium, ) and that mice deficient in bikunin (Ambp/bikunin knockout mice) exhibit specific behavioral phenotypes such as increased anxiety‐like behavior (Goulding et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study has suggested that baseline delta sleep ratio is a useful predictor for the antidepressant effects of ketamine ( Duncan et al, 2013a ). These and other observations have led to hypotheses proposing that the interplay of increased synaptic strength and the neurobiological processes that occur during SWA is important for the emergence of rapid antidepressant effects as well as their sustainability ( Duncan et al, 2019 ; Goldschmied and Gehrman, 2019 ; Rantamäki and Kohtala, 2020 ; Wolf et al, 2016 ). The clinical relevance of these ideas, however, remains to be thoroughly tested.…”
Section: Sleep Depression and Rapid-acting Antidepressantsmentioning
confidence: 99%
“…Interestingly, delta oscillations during sleep have been proposed as a homeostatic mechanism to rescale the potentiation in synaptic strength that occurs with prolonged wakefulness (Tononi and Cirelli, 2003). This mechanism is disrupted in patients with depressive disorders, possibly leading to the cognitive impairments seen in this population (Goldschmied and Gehrman, 2019). Optogenetic manipulations of delta rhythms during sleep and subsequent tests of synaptic plasticity (both in vitro and in vivo) provide exciting opportunities to test these hypotheses (Durkin et al, 2017).…”
Section: Addressing Oscillations With Optogeneticsmentioning
confidence: 99%